2001
DOI: 10.1095/biolreprod64.1.396
|View full text |Cite
|
Sign up to set email alerts
|

Rat Seminiferous Epithelium Contains a Unique Junction (Ectoplasmic Specialization) with Signaling Properties Both of Cell/Cell and Cell/Matrix Junctions

Abstract: The seminiferous epithelium contains unique actin related cell-cell junctions, termed ectoplasmic specializations (ESs). Turnover of these junctions is fundamental to sperm release and to movement of spermatocytes from basal to adluminal compartments of the epithelium during spermatogenesis. In this study we report several novel observations related to the spatial and temporal distribution of integrin-related signaling molecules at ESs. We confirm the presence of beta(1)-integrin at these sites and further dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
181
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(196 citation statements)
references
References 27 publications
14
181
1
Order By: Relevance
“…Nevertheless, it is interesting to note that there are no reported cases of hemidesmosome disassembly in the testis, suggestive of stable and robust adhesion. Moreover, ␣6␤1 integrin does not seem to localize to the intermediate filament-based hemidesmosome in the testis but apparently to the actin-based basal ectoplasmic specialization (Chapin et al, 2001;Mulholland et al, 2001). In addition, except for a single report published nearly 2 decades ago that described the presence of an uncharacterized 120-kDa protein in the testis referred to as 1-2B7B (Zhang et al, 1991), there has been no advancement in the biology of the hemidesmosome in this organ.…”
Section: Cell-matrix Intermediate Filament-based Hemidesmosomesmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, it is interesting to note that there are no reported cases of hemidesmosome disassembly in the testis, suggestive of stable and robust adhesion. Moreover, ␣6␤1 integrin does not seem to localize to the intermediate filament-based hemidesmosome in the testis but apparently to the actin-based basal ectoplasmic specialization (Chapin et al, 2001;Mulholland et al, 2001). In addition, except for a single report published nearly 2 decades ago that described the presence of an uncharacterized 120-kDa protein in the testis referred to as 1-2B7B (Zhang et al, 1991), there has been no advancement in the biology of the hemidesmosome in this organ.…”
Section: Cell-matrix Intermediate Filament-based Hemidesmosomesmentioning
confidence: 91%
“…Generally speaking, numerous studies have linked focal contact function to cell spreading and migration. Although the existence of focal contacts in the testis has never been described, several studies from different laboratories have reported the presence of putative focal contact proteins in this organ, including ␣6␤1 integrin (Salanova et al, 1995(Salanova et al, , 1998Mulholland et al, 2001), integrin-linked kinase [ILK (Mulholland et al, 2001)], focal adhesion kinase [FAK (Siu et al, 2003)], c-Src Zhang et al, 2005), vinculin (Grove et al, 1990;Pfeiffer and Vogl, 1991), profilin III (Braun et al, 2002), talin (Santoro et al, 2000), paxillin (Wine and Chapin, 1999), zyxin , fimbrin (Grove and Vogl, 1989), and laminin (Koch et al, 1999;Siu and Cheng, 2004a;Yan and Cheng, 2006). It is noteworthy that many of these focal contact proteins were shown to localize to the ectoplasmic specialization rather than at the Sertoli cell-basement membrane interface, as expected.…”
Section: Cell-matrix Actin-based Focal Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…␤1-Integrin and ␣6-integrin form a functional adhesion complex of ␣6␤1-integrin at the apical ES residing in Sertoli cells (9,10,15), and ␣6␤1-integrin is the receptor of laminin-333 residing in elongating/elongated spermatids (3,11). However, the precise localization of ␤1-integrin at the basal compartment is not well defined.…”
Section: Localization Of ␤1-integrin In the Seminiferous Epithelium Omentioning
confidence: 99%
“…For instance, ␤1-integrin was reported to be a component of the basement membrane in the seminiferous tubules (14), perhaps at the hemidesmosomes. Others have reported its localization with the actin-based anchoring junction structure (i.e., basal ES) at the BTB (10,15). It is also not known whether there is cross-talk between ␤1-integrin in the apical ES, the BTB, and hemidesmosome.…”
mentioning
confidence: 99%